AN ANALYSIS OF THE WAY IN DECIDING BETWEEN LOVE AND SELF ESTEEM IN GNOMEO AND JULIET MOVIE - CHRISNARI, SISKA TYAS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Psychological, self esteem.This research is focus on psychological conflict that underwent by the main characters on Gnomeo and Juliet Movie Cartoon.  This movie cartoon tells about the two families, The Blues and The Reds that are rival. They always be the best and reach a higher social class to show their self esteem. But, unintentionally their children met and fallen in love each other. Finally, their children named Gnomeo and Juliet have promises’ to live together.Because of that, the main characters have the problem in Deciding between love and self-esteem, and the researcher uses the theory of Abraham Maslow to reveal this problem. In this theory, the researcher tries to know the steps that taken by the main characters in choosing between their love and self-esteem.Based on the analysis, the researcher finds that there are three steps that taken by the main characters to reveal their problem. The first steps is that they realize that they fallen in love each other. The second step is they realize that their love is above everything and the last or the third step is that they struggle to proof that love can make everything better.